Acculturative stress, quality of life and its relationship with sociodemographic variables in Venezuelan immigrants - Huamani López, Yashumi Raquel (2023)
The crisis in Venezuela has led a large number of citizens to migrate to different countries, including Peru; however, this has brought with it a series of challenges in terms of physical and mental health for Venezuelan migrants. Given this situation, the present research aims to examine the relationship between acculturative stress, health-related quality of life and sociodemographic variables such as age, sex, type and hours of work, as well as having legal documents in force. A non-experimental and cross-sectional study was carried out, the sample was composed of 608 Venezuelan migrants, who were selected through a non-probabilistic snowball sampling. The results obtained showed significant relationships between acculturative stress and health-related quality of life (physical and mental health). Similarly, older immigrants who have legal documents, work longer hours, and have informal employment tend to report higher acculturative stress. In turn, women tend to report higher physical and mental health than men. These findings highlight the importance of implementing measures to improve the experience of Venezuelan migrants in Peru by providing comprehensive support that addresses both psychological and labor needs, with the objective of helping migrants face challenges in the adaptation process and promoting their overall well-being.